The study on Malaysia Agricultural E-Commerce (AE): Customer Purchase Intention - Wah Hen, Kai; Seah, Choon Sen; Witarsyah, Deden; Shaharudin, Shazlyn Milleana; Xia Loh, Yin (Society of Visual Informatics, 2023)
Electronic commerce (E-Commerce) became an essential trading platform after the Covid-19 pandemic. From essential products to luxury brands, consumers can find almost everything on the normal E-Commerce platforms with the exception of fresh agricultural products. Agricultural E-Commerce (AE) is introduced to overcome the market needs. Technology Acceptance Model (TAM) is studied and integrated with additional variables to determine the needs of AE in Malaysia. In this study, five variables (product quality, logistic service quality, perceived price & value, platform design quality, and platform security) were studied to determine the Malaysian consumers’ purchase intention towards the AE. Five hypotheses were developed to identify the relationship between the variables. A total of 300 AE users have contributed their perception as respondents in this study through a survey questionnaire. The collected data were processed before the data analysis via Statistical Package for The Social Science (SPSS) version 25.0. Descriptive analysis, and inferential analysis were conducted. The result shows that all five variables are significantly related to the purchase intention towards AE. The product quality has the highest significant value (0.805) towards the purchase intention on AE, followed by logistic service quality, platform security, platform design quality and perceived price and value. Implication, limitation, and recommendation were also being discussed to assist the AE stakeholders in improving their AE.